2022
DOI: 10.1037/dev0001330
|View full text |Cite
|
Sign up to set email alerts
|

Distinctions between moral and conventional judgments from early to middle childhood: A meta-analysis of social domain theory research.

Abstract: Understanding distinctions between morality and conventions is an important milestone in children’s moral development. The current meta-analysis integrated decades of social domain theory research (Smetana, 2006; Turiel, 1983) on moral and conventional judgments from early to middle childhood. We examined 95 effect sizes from 18 studies (2,707 children; Mage = 7.30 years; 51% females; 42% Whites). Along with these, effects from additional 28 studies were estimated with imputed correlations in a secondary analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Similarly, research based on social domain theory has found that as children age, they become more able to consider contextual factors such as intentions and mitigating circumstances in judging whether an interpersonal transgression was morally wrong and whether the transgressor had a right to act the way they did (e.g., Nucci et al, 2017). Taken together, this work suggests that individuals' propensity to consider the social context in determining whether their own actions constitute an interpersonal transgression increases with age (Yoo & Smetana, 2022).…”
Section: Interpersonal Transgressionsmentioning
confidence: 53%
“…Similarly, research based on social domain theory has found that as children age, they become more able to consider contextual factors such as intentions and mitigating circumstances in judging whether an interpersonal transgression was morally wrong and whether the transgressor had a right to act the way they did (e.g., Nucci et al, 2017). Taken together, this work suggests that individuals' propensity to consider the social context in determining whether their own actions constitute an interpersonal transgression increases with age (Yoo & Smetana, 2022).…”
Section: Interpersonal Transgressionsmentioning
confidence: 53%
“…While past work suggests there is a close relation between descriptive and injunctive norms, the strength of that relation might vary depending on the kind of behavior in question. There is now a sizeable body of work on social domain theory which finds an important distinction between moral norms, which are universally applied and obligatory, and social conventional norms, which are perceived as subjective and alterable, finding that by age 4 children start to consistently differentiate between these behaviors (Killen et al, 2006;Smetana, 2013;Yoo & Smetana, 2022). Indeed, recent work with adults suggests that the effect of descriptive norms on injunctive norm beliefs varies depending on the kind of norm, such that people are generally less sensitive to descriptive norms for harm behaviors than conventional or fairness behaviors (Deutchman et al, preprint).…”
Section: Differences Between Norm Categoriesmentioning
confidence: 99%
“…Social norms are a foundational part of human societies and pervade nearly every aspect of social life-from how we eat and dress to how we share resources. A large body of work has found that children and adults acquire, conform, and enforce social norms across a diverse range of contexts and behaviors, including social conventions (Song et al, 1987;Yoo & Smetana, 2022), moral behaviors (Vaish et al, 2011;Yucel & Vaish, 2018), sharing resources (House, 2018;McAuliffe et al, 2017;McQuire et al, 2018), and playing games (Diesendruck & Markson, 2011;Kanngiesser et al, 2022;Langenhoff et al, 2022;Rakoczy et al, 2008). How are we able to acquire these different kinds of norms?…”
Section: Introductionmentioning
confidence: 99%
“…Children are capable of critically evaluating teachers' actions, such as when they punish the group for the misdeeds of one child (Piaget, 1932(Piaget, /1965 or condone acts of moral transgressions, such as inflicting harm on another person (Smetana et al, 2012). As well, children recognize the domains of student behavior that fall within and without a teacher's legitimate authority (Guerrero et al, 2017;Smetana & Bitz, 1996;Yoo & Smetana, 2022). In general, children view moral judgments as obligations that apply across scenarios, not as a matter of consensus, nor as under authority jurisdiction (Turiel, 1983(Turiel, , 2002.…”
Section: Children's Critical Social-cognitive and Moral Capacitiesmentioning
confidence: 99%